Geriatric Nutrition: the health professionals handbook - Chernoff, Ronni (Burlington: Jones and Bartlett Learning, 2014)
A authoritative reference written to help professionals understand the role of nutrition in the maintenance of health, the management of chronic conditions, and the treatment of serious Illness. The fourth edition of this text provides a comprehensive review of nutritional assessment, intervention programs for the elderly, and health promotion activities
State Grant 2016-2017
Includes bibliographical references and index.
Keywords: OLDER PEOPLE --NUTRITION; NUTRITION DISORDERS IN OLD AGE; AGING - PHYSIOLOGY